2019
DOI: 10.1039/c9ta04763h
|View full text |Cite
|
Sign up to set email alerts
|

Porous NiTiO3/TiO2nanostructures for photocatatalytic hydrogen evolution

Abstract: Porous NiTiO3/TiO2 heterostructures prepared from the annealing in air of TiO2 : Ni nanoneedle bundles displayed excellent photocatalytic activity toward hydrogen generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The bandgap energy of the 33ATO/Ti, ATO, and TiO 2 (w) was calculated by the Tauc plot and exhibited the values of 3.06, 3.42 [22], and 3.14 eV [16], respectively. A similar conclusion was reported by Xing et al, and the introduction of NiTiO 3 enhanced the photocatalytic properties of TiO 2 as the surface area, light absorption, and charge separation [13]. These researches have confirmed that the particle size has an important effect on the catalyst properties.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The bandgap energy of the 33ATO/Ti, ATO, and TiO 2 (w) was calculated by the Tauc plot and exhibited the values of 3.06, 3.42 [22], and 3.14 eV [16], respectively. A similar conclusion was reported by Xing et al, and the introduction of NiTiO 3 enhanced the photocatalytic properties of TiO 2 as the surface area, light absorption, and charge separation [13]. These researches have confirmed that the particle size has an important effect on the catalyst properties.…”
Section: Resultssupporting
confidence: 85%
“…The results elucidated that SrTiO 3 -TiO 2 boosted the separation efficiency of the photogenerated charge carriers [14]. Also, the porous NiTiO 3 /TiO 2 catalyst, synthesized by a hydrothermal route, exhibited excellent performance such as high surface area, high light absorption, and efficient charge separation for photocatalytic hydrogen generation [13]. Huang et al found that NiTiO 3 was an effective cocatalyst, which improved the photocatalytic activity of TiO 2 on the heterostructural NiTiO 3 /TiO 2 nanotubes [15].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, given the limitation of current battery technology, methods to store sunlight for long duration and at large scale are still needed. Instead, solar energy can be directly converted into chemical fuels, for instance hydrogen from water splitting or carbon‐based products from carbon dioxide reduction, using a semiconductor/electrolyte junction in a photoelectrochemical cell . Indeed, photoelectrochemical (PEC) hydrogen production has garnered growing attention ever since the first demonstration of photocatalytic water splitting on TiO 2 surface .…”
Section: Introductionmentioning
confidence: 99%
“…The UV–visible light source contained two LEDs emitting at 372 ± 5 nm and two LEDs emitting visible light (correlated color temperature, 6099 K; color rendering index, 74; Figure S21). In this system, light irradiation at the sample position was 11.2 ± 0.5 mW·cm –2 for UV light and 0.017 ± 0. , 005 mW·cm –2 for visible light. ,, …”
Section: Methodsmentioning
confidence: 99%